Effectiveness Of Individual Counseling To Improve Student Social Interaction Through Sociometry" (Case Study In Unggul Sigli State High School Students) - Fauzi Aldina; Muqqarramah Fitri; Zamratul aini; Rizka Heni (Journal Of Social Science (JoSS), 2022)
Social interaction is a dynamic social relations. Social relations in question can be in the form of one individual relationship with another individual, between one group and another, or between groups and individuals. In interaction there are also symbols, where a symbol is defined as something whose value or meaning is given to those who use it. This study aims to find out how students can interact socially using sociometry and also assisted with counseling services. The research method used in this study is a qualitative descriptive method, namely research that seeks to increase students' social interaction using sociometry. The results of the study can be stated that there are some students whose interactions are not good, but because this study uses follow-up in the form of group counseling.